Direct observation of key photoinduced dynamics in a potential nano-delivery vehicle of cancer drugs. Issue 1 (5th November 2014) - Sardar, Samim; Chaudhuri, Siddhi; Kar, Prasenjit; Sarkar, Soumik; Lemmens, Peter; Pal, Samir Kumar
Abstract : The crucial photoinduced dynamics in ZnO nanoparticles (NPs) upon complexation with the cancer drug protoporphyrin IX (PP). Abstract : In recent times, significant achievements in the use of zinc oxide (ZnO) nanoparticles (NPs) as delivery vehicles of cancer drugs have been made. The present study is an attempt to explore the key photoinduced dynamics in ZnO NPs upon complexation with a model cancer drug protoporphyrin IX (PP). The nanohybrid has been characterized by FTIR, Raman scattering and UV-Vis absorption spectroscopy. Picosecond-resolved Förster resonance energy transfer (FRET) from the defect mediated emission of ZnO NPs to PP has been used to study the formation of the nanohybrid at the molecular level. Picosecond-resolved fluorescence studies of PP–ZnO nanohybrids reveal efficient electron migration from photoexcited PP to ZnO, eventually enhancing the ROS activity. The dichlorofluorescin (DCFH) oxidation and no oxidation of luminol in PP/PP–ZnO nanohybrids upon green light illumination unravel that the nature of ROS is essentially singlet oxygen rather than superoxide anions. Surface mediated photocatalysis of methylene blue (MB) in an aqueous solution of the nanohybrid has also been investigated. Direct evidence of the role of electron transfer as a key player in enhanced ROS generation from the nanohybrid is also clear from the photocurrent measurement studies. We have also used the nanohybrid in a model photodynamic therapy application in a light sensitized bacteriological culture experiment.